2024
DOI: 10.1002/slct.202400788
|View full text |Cite
|
Sign up to set email alerts
|

Thermoreversible Transformations of the Cyanosubstituted 2‐Oxopyrrole Derivative by the Action of Amines for the Creation of Novel High‐Contrast Coloration/Decoloration Systems

Mikhail Yu. Belikov,
Angelina G. Milovidova,
Mikhail Yu. Ievlev

Abstract: A new efficient approach to the synthesis of intensely colored 2‐(2‐oxo‐3H‐pyrrol‐3‐ylidene)malononitrile (OP) was developed. Using the reaction of OP with amines, a series of previously unknown colorless organic salts – dicyano(2‐oxo‐2,5‐dihydro‐1H‐pyrrol‐3‐yl)methanides were synthesized, bearing in the structure two fragments of same or diverse amines of different nature (covalent and ionic). TGA‐DTA study of the synthesized salts showed a thermal reversibility of their formation. The introduction of violet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 44 publications
2
6
1
Order By: Relevance
“…It should be noted that, in contrast to our previous work, 38 the isolation of the forms 2a-C5 and 2a-Q for compound 2a turned out to be impossible. We associate this with the presence of an electron-donating OH group in the structure of 2a , which slightly deactivates the C5 atom of the pyrrole ring for nucleophilic addition compared to an analogue of 2a without an OH group.…”
Section: Resultscontrasting
confidence: 98%
See 4 more Smart Citations
“…It should be noted that, in contrast to our previous work, 38 the isolation of the forms 2a-C5 and 2a-Q for compound 2a turned out to be impossible. We associate this with the presence of an electron-donating OH group in the structure of 2a , which slightly deactivates the C5 atom of the pyrrole ring for nucleophilic addition compared to an analogue of 2a without an OH group.…”
Section: Resultscontrasting
confidence: 98%
“…Moreover, structures F were successfully isolated as salts and could be thermally converted into analogues of pyrroles 2 without the OH moiety. 38 We also experimentally confirmed that the process of iminofuran C rearrangement into lactam 2 did not occur without an intermediate nucleophilic addition. For this, OTC 1a was treated with N -methylmorpholine under the same reaction conditions, but the formation of compound 2a was not observed.…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations